Thermomechanical processing of In-containing β-type Ti-Nb alloys. (March 2018) - Pilz, Stefan; Geissler, David; Calin, Mariana; Eckert, Jürgen; Zimmermann, Martina; Freudenberger, Jens; Gebert, Annett
Abstract: In this study, the effect of thermomechanical processing on microstructure evolution of the indium-containing β-type Ti alloys (Ti-40Nb)-3.5In and (Ti-36Nb)-3.5In was examined. Both alloys show an increased β-phase stability compared to binary alloys due to In additions. This leads to a reduced α''-phase fraction in the solution treated and recrystallized state in the case of (Ti-36Nb)-3.5In and to the suppression of stress-induced α'' formation and deformation twinning for (Ti-40Nb)-3.5In. The mechanical properties of the alloys were subsequently studied by quasistatic tensile tests in the recrystallized state, revealing reduced Young's modulus values of 58 GPa ((Ti-40Nb)-3.5In) and 56 GPa ((Ti-36Nb)-3.5In) compared to 60 GPa as determined for Ti-40Nb. For both In-containing alloys the ultimate tensile strength is in the range of 560 MPa. Due to the suppressed α'' formation, (Ti-40Nb)-3.5In exhibits a linear elastic deformation behavior during tensile loading together with a low Young's modulus and is therefore promising for load-bearing implants.